Higher education in Gerodontology in European Universities - Anastassia Kossioni; Gerry McKenna; Frauke Müller; Martin Schimmel; Jacques Vanobbergen (BMC, 2017)
Abstract Background The rapid aging of the European population and the subsequent increase in the oral care needs in older adults necessitates adequate training of dental professionals in Gerodontology (Geriatric Dentistry). This study was designed to investigate the current status of Gerodontology teaching amongst European dental schools at the undergraduate, postgraduate and continuing education levels. Methods An electronic questionnaire was developed by a panel of experts and emailed to the Deans or other contact persons of 216 dental schools across 39 European countries. The questionnaire recorded activity levels, contents and methodology of Gerodontology teaching as part of dental education programs. Repeated e-mail reminders and telephone calls were used to encourage non-responders to complete the questionnaire. Results A total of 123 responses from 29 countries were received (response rate: 56.9%). Gerodontology was taught in 86.2% of schools at the undergraduate level, in 30.9% at the postgraduate level and in 30.1% at the continuing education level. A total of 43.9% of the responding schools had a dedicated Gerodontology program director. Gerodontology was taught as an independent subject in 37.4% of the respondent schools. Medical problems in old age, salivary impairment and prosthodontic management were the most commonly covered topics in Gerodontology teaching. Clinical teaching took place in 64.2% of the respondent schools, with 26.8% offering clinical training in outreach facilities. Conclusions The vast majority of European dental schools currently teach Gerodontology at the undergraduate level. More training opportunities in oral care of frail elders should be offered, and more emphasis should be placed on interdisciplinary and interprofessional training, educational collaborations, and the use of modern technologies. Dedicated postgraduate Gerodontology courses need to be developed to create a significant number of specialized dentists and trained academics.